Nutritional therapy of autism children (Research, Society and Development, 2023)
Autism has been a much discussed topic lately, mainly due to the increase in the number of confirmed childhood autism diagnoses, according to the WHO (World Health Organization) about 2 million Brazilians are autistic. The diet of these children must be studied and analyzed very carefully, due to the various food restrictions, both in terms of texture, smell and even the shape of the food. The aim of this study was to verify whether nutritional therapy can help with the symptoms of autistic children, that is, how healthy eating can help these children. Analyzing the influence of gluten, casein and lactose in the diet of autistic children, showing their results for the intestinal microbiota and for the behavior of individuals. In addition to demonstrating how the food selectivity of these children works, highlighting the importance of a food introduction for them. It was found that gluten-free and casein-free diets (SGSC), which are known to restrict gluten and casein, in some studies, are responsible for significant improvement in social aspects, reducing hyperactivity and attention deficit, consequently influencing the increase in considerable amount of social interactions and a decrease in eating disorders. On the other hand, there were studies that did not show any kind of significant improvement, highlighting the importance of nutritional monitoring by professionals, thus avoiding nutritional deficiencies. For this study, scientific articles, legal documents, magazines and health notebooks were used. Another method addressed was also the choice of articles from the last 10 years, so that the information was relatively up-to-date, prioritizing articles in English and Portuguese.